Apples - Farmer, Jacqueline; Tildes, Phyllis Limbacher (Watertown, Mass. : Charlesbridge, 2007)
Provides a variety of information on apples including care of apple trees, the history and folklore of the apple, and the ways apples are used when they are harvested.
Includes bibliographical references.
Keywords: Apples -- Juvenile literature